2017
DOI: 10.1177/0886260517739290
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Study of the Impact of Intimate Partner Violence Primary Aggressor Laws on Single and Dual Arrest

Abstract: The adoption of arrest as the preferred response in incidents of intimate partner violence has generally been welcomed, but it has not come without unintended consequences. Foremost among these has been an increase in dual arrest, the situation where both parties to an incident are arrested. To address this concern, many states have enacted primary aggressor laws which mandate that officers determine who is the primary aggressor in the incident. To date, no longitudinal national study has been conducted on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 46 publications
3
27
0
1
Order By: Relevance
“…These results expand in a number of ways on previous research which has indicated that incidents with same-sex couples are less likely than those with opposite-sex couples to result in arrest and are substantially more likely to result in both parties being arrested (Hirschel et al, 2021). First, there is some comfort in noting that there was no significant difference among the couples in the likelihood of arrest for aggravated assault and overall a reduced likelihood of dual arrests as the severity of the offense increased.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…These results expand in a number of ways on previous research which has indicated that incidents with same-sex couples are less likely than those with opposite-sex couples to result in arrest and are substantially more likely to result in both parties being arrested (Hirschel et al, 2021). First, there is some comfort in noting that there was no significant difference among the couples in the likelihood of arrest for aggravated assault and overall a reduced likelihood of dual arrests as the severity of the offense increased.…”
Section: Discussionsupporting
confidence: 73%
“…Due to the confounding nature of characteristics found in cases in which there are multiple victims and offenders, cases with more than two victims and more than two offenders were omitted. This approach is consistent with NIBRS research examining the likelihood of crime clearance (see, for example, Hirschel et al, 2021;McCormack & Hirschel, 2018;Roberts & Lyons, 2011;Walfield, 2016). As a result, the sample was reduced in size by 49,445 (1.8%) cases and 13 (0.2%) jurisdictions.…”
Section: Datasupporting
confidence: 77%
See 2 more Smart Citations
“…Arrests of women for IPV/A-related charges have increased dramatically (Hovmaud, Ford, Flom, & Kyriakakis, 2009; Meloy & Miller, 2001). Yet research demonstrates that men are disproportionately the offenders in IPV/A cases, and women are overwhelmingly the victims of men’s violence (Chesney-Lind, 2002; Hirschel, McCormack, & Buzawa, 2017; Rennison, 2003). Ostensibly, gender-neutral arrest policies often fail to identify the primary aggressor and instead punish victims who may use force in defense of self or children or for other reasons—but women’s actions rarely terrify and control their male partners in the same way recognized in male-to-female intimate violence scenarios (Goodmark, 2012; Miller, 2005).…”
Section: Introductionmentioning
confidence: 99%